Health impact assessment of coal-fired boiler retirement at the Martin Drake and Comanche power plants - Martenies, Sheena, author; Gan, Ryan, author; Magzamen, Sheryl, author; Akherati, Ali, author; Jathar, Shantanu, author (Colorado State University. Libraries, 2018)
Health impact assessment (HIA) is a suite of tools used to characterize potential health effects of policies, projects, or regulations. The objective of this HIA was to understand the impact of decommissioning units at two large coal-fired power plants on mortality and morbidity in the Southern Front Range region of Colorado. Based on Community Multiscale Air Quality (CMAQ) chemical transport models of fine particulate matter with an aerodynamic diameter less than 2.5 μm (PM2.5) and ozone (O3), we modeled five potential emissions reductions scenarios and estimated the potential health benefits of reduced exposures to PM2.5 and ozone for premature deaths, cardiovascular and respiratory hospitalizations, and other health outcomes for ZIP codes in the Southern Front Range region, including the cities of Denver, Colorado Springs, and Pueblo. Health Benefits Scenarios 1 and 2 estimated the health benefits of shutting down most units at the Comanche plant in Pueblo, CO (one newer unit remained operational) relative to a baseline scenario using emissions from 2011 (Scenario 1) or a counterfactual baseline scenario that accounted for sulfur dioxide emissions controls (scrubbers) installed at the Martin Drake plant in Colorado Springs in 2016 (Scenario 2). Health Benefits Scenario 3 estimated the benefits of shutting down the Martin Drake plant relative to the 2011 baseline. Health Benefits Scenario 4 estimated the health benefits of shutting down the Martin Drake power plant and shutting down all but one boiler at the Comanche power plant relative to a 2011 emissions baseline. Health Benefits Scenario 5 estimated the marginal health benefits of decommissioning these plants (with one remaining coal-fired boiler at Comanche) relative to a counterfactual baseline year that considered emissions controls installed at the Martin Drake facility in 2016. In addition to estimating the number of deaths, hospitalizations, and other health outcomes that would potentially be avoided by reducing emissions at these facilities, we also estimated the monetary impact using outcome valuations typically used in US EPA health benefits analyses and examined the environmental justice implications of reduced emissions and exposures across the Southern Front Range. • For Health Benefits Scenario 1 (Comanche Units 3 and 4 were “zeroed out” and compared to a baseline where all other emissions were at 2011 levels), we estimated that reducing population exposures to PM2.5 would result in 1 (95% CI: 0 - 1) fewer premature death each year. Reductions in PM2.5 and O3 exposures would also result in fewer restricted activity days among adults [5 (95% CI: -3 – 95)] and fewer missed school days for children [27 (95% CI: -19- 582)]. Benefits of retiring the Comanche units were similar when emissions controls at Martin Drake are taken into account (Health Benefits Scenario 2). • For Health Benefits Scenario 3 (emissions at Martin Drake were “zeroed out”), we estimated that reducing population exposures to PM2.5 and O3 would result in 4 (95% CI: 2 - 5) and < 1 (95% CI: 0 - 1) fewer premature deaths each year, respectively. Reductions in PM2.5 and O3 exposures would also result in fewer restricted activity days among adults [10 (95% CI: 0 – 74)] and fewer missed school days for children [4 (95% CI: 2- 5)]. • For Health Benefits Scenario 4, we estimated that reducing population exposures to PM2.5 and O3 would result in 4 (95% CI: 2 - 6) and < 1 (95% CI: 0 - 1) fewer premature deaths each year, respectively. Among the largest annual health benefits are avoided asthma symptom days among children [16 (95% CI: -1 – 141) due to PM2.5 and 13 (95% CI: -348 - 972) due to O3] and minor restricted activity days among adults [69 (95% CI: 0 - 488) due to PM2.5 and 71 (95% CI: -31 - 750) due to O3]. We also estimated that, for Health Benefits Scenario 1, children in the study area would miss 77 (95% CI: -77 - 1180) fewer days of school each year due to lower O3 exposures. • Annual health benefits were lower for Health Benefits Scenario 5 compared to Scenario 4 due to the smaller change in exposure concentration after accounting for the control technologies installed at Martin Drake in 2016. For Health Benefits Scenario 5, we estimated that reducing population exposures to PM2.5 and O3 would result in 2 (95% CI: 1 - 3) and < 1 (95% CI: 0 - 1) fewer premature deaths each year, respectively. Other annual benefits under Health Benefits Scenario 2 included 2 (95% CI: -17 – 44) and 9 (-242 – 678) avoided asthma symptom days due to PM2.5 and O3 exposures, respectively; 28 (95%CI: -2 – 188) and 48 (95%CI: -16 – 513) minor restricted activity days due to PM2.5 and O3 exposures; and 53 (95% CI: -48 – 833) avoided school absences among children due to O3 exposures. • Monetized health benefits when both plants were “zeroed out” ranged from $4.2 million (95% CI: $2.1 million - $7.2 million) for Health Benefits Scenario 4 to $1.7 million (95% CI: $0.8 million – 3.2 million) for Health Benefits Scenario 5. Benefits tended to be smaller when only one plant was considered. In all of the analyses, the monetized impacts were driven by the value of avoided premature mortality. In addition, we found that ZIP codes with lower median incomes tended to receive a greater share of the health benefits of decreasing exposures to PM2.5 and O3 resulting from power plant shutdowns. This finding suggests that reducing emissions at the power plants could potentially alleviate some environmental justice concerns in the area.
Keywords: health impact assessment; coal-fired power plants; environmental justice